Restoration approach of 3D ultrasound images using complex wavelet-based Laplacian-TV mixture prior. Issue 6 (2nd November 2017) - Uddin, Muhammad Shahin; Islam, Rafiqul; Tahtali, Murat; Lambert, Andrew J.; Pickering, Mark R.; Marchese, Margaret; Stuart, Iain
Abstract : 3D ultrasound imaging has advantages over other medical imaging modalities, as it does not involve invasive measurements, reduces study time and operator dependency and can display volume information in real time. It is a valuable way of examining many of the body's internal organs; however the visibility of details of the organs are usually degraded by speckle noise and blurring during the image acquisition process. A number of image restoration methods have been used to reduce the effects of blurring and noise. Most of the restoration methods involve the use of a prior model as a regularisation term to solve an ill-posed inverse problem. In this paper, we present a wavelet-based restoration method for 3D ultrasound image restoration where a Laplacian scale mixture model combined with a total variation constraint is used as a regularisation prior. Our results show that the restored 3D ultrasound volumes produced by this approach have improved quality over those restored using other recently proposed approaches.